VARIASI BERAT ROLLER TERHADAP PERFORMA PADA SEPEDA MOTOR HONDA SCOOPY FI TAHUN 2016 - Aldi, Antoro; Anam, Khoirul (Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
Along with the rapid development of science and technology at this time, it has an impact on the development of the industrial world, especially in the automotive industry. The increasing number of human population in Indonesia demands the development of the provision of transportation facilities, one of the means of transportation that is widely used by the community is motorbikes. Given the ever-increasing need, motorcycle manufacturers are now competing to produce new motorcycles with various advantages, both in terms of design and technological advantages. Motorcycle manufacturers develop motorcycle components in order to achieve efficiency and good quality. The purpose of this study was to determine how much influence the use of 11 gram, 12 gram and 13 gram roller weight variations on the speed of the 2016 Honda Scoopy FI motorcycle. The test was carried out using a Dynoster tool by changing the roller weight according to the weight to be tested alternately then prepare the. The results of the test show that the roller weight with a weight of 11 grams is the best to use.Keywords: Roller Weight, Power and Torque